From Climate Model Output to Actionable Climate Information in Norway - Nilsen, Irene Brox; Hanssen-Bauer, Inger; Dyrrdal, Anita Verpe; Hisdal, Hege; Lawrence, Deborah; Haddeland, Ingjerd; Wong, Wai Kwok (Frontiers in Climate, 2022)
The Norwegian Centre for Climate Services (NCCS) has developed a production chain for climate information with the aim of delivering a knowledge base for climate change adaptation suitable for use by planners at various administrative levels in Norway. This process consists of two main steps: First, climate and hydrological projections are produced at a local scale (1 × 1 km resolution) using available results from global and regional climate models (GCMs and RCMs). In a second step, climate factsheets with abridged information relevant for individual counties in Norway have been co-produced with users and county authorities. Projections were produced by using a climate–hydrological modeling chain driven by downscaled simulations from 10 GCM–RCM combinations and two climate scenarios in which temperature and precipitation were first downscaled and bias-adjusted to a 1 × 1 km resolution. Bias-adjustment was necessary, partly due to biases in the RCMs. These results were published in the Norwegian climate assessment report “Climate in Norway 2100.” The results have then been disseminated through various formats, such as reports, dataportals, visualizations and factsheets (available at https://klimaservicesenter.no/). NCCS has issued climate factsheets for 17 counties in Norway and Svalbard. The county-wise climate factsheets have become the most extensive product issued by NCCS. A challenge when developing information about climate change for use in adaptation is the issue of uncertainty, and the trade-off between robustness vs. precision in the numerical values given should guide the dissemination of climate information. Based on our experiences, we also recommend that climate information is developed in collaboration with users because this ensures that it will be understood by a wider audience. Most climate-related challenges for infrastructure are related to extreme events. For technical applications in Norway, climate change allowances are now available for heavy precipitation, floods, and storm surges as a tool for design analyses of buildings and infrastructure. This paper describes the production chain for the presently available climate projections following the release of IPCC AR5 (CMIP5), our experiences of the dissemination process, as well as our plans for further development of the next national climate assessment report based on IPCC AR6 (CMIP6).